The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/1413-81232023281.09882022en
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of women who have sex with women about Sexually Transmitted Infections and AIDS

Abstract: This article aims to study the knowledge of women who have sex with women about Sexually Transmitted Infections and AIDS. Cross-sectional study of 260 women, 81 women who either have sex with women or with men and women (WSW) and 179 women who have sex exclusively with men (WSM). Data were collected in 2019/2020 by means of a form and validated instruments. To study the association between sexual partnership and level of knowledge about Sexually Transmitted Infections and AIDS, multiple Cox regression models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…It should be noted here that many previous studies showed a significant lack of women's knowledge about STDs worldwide. Furthermore, the lack of knowledge was not related to one category of women, as studies have shown an STD knowledge deficit among women of all ages and social classes, as well as pregnant and bisexual ladies (Baldeh & Isara, 2019;Ekşi & Kömürcü, 2014;Kowalczyk & Nowosielski, 2019;Parenti et al, 2023;Volck et al, 2013;Zizza et al, 2021). Concerning Muslim culture, one systematic review of several studies also showed the lack of STD knowledge among women.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted here that many previous studies showed a significant lack of women's knowledge about STDs worldwide. Furthermore, the lack of knowledge was not related to one category of women, as studies have shown an STD knowledge deficit among women of all ages and social classes, as well as pregnant and bisexual ladies (Baldeh & Isara, 2019;Ekşi & Kömürcü, 2014;Kowalczyk & Nowosielski, 2019;Parenti et al, 2023;Volck et al, 2013;Zizza et al, 2021). Concerning Muslim culture, one systematic review of several studies also showed the lack of STD knowledge among women.…”
Section: Introductionmentioning
confidence: 99%